Numerical method for shape optimization of standard floor of the high-rise buildings in hot-summer and cold-winter areas under the low energy consumption target—taking the L-shape as an example - X.Y. Ying; W.Z. Li; Q. Kan; Z. Zhang; G. Ding (Lowland Technology International, 2018)
Shape is an important consideration in building design due to its significant impact on building performance in energy consumption. This paper presents a methodology to program planes using MATLAB language. Three side length factors were proposed as the design variables for L-shaped layouts, and eighteen kinds of L-shaped layouts were generated by changing those variables individually. An energy consumption simulation software (DesignBuilder) was developed to simulate the energy consumption of these layouts of high-rise buildings as experimental models. The correlativity between the width ratio and depth ratio of all experimental models and their energy consumption was examined when deriving the corresponding polynomial function. The main finding of the study suggested that there were certain critical points for both width ratio and depth ratio of the standard floor of high-rise buildings with Lshaped plane, which was 0.4 for width ratio and 0.67 for depth ratio. The energy consumption increased rapidly beyond the critical point, and there was a slight fluctuation at another interval. Further, this paper provided a range of side length ratio in contour plots which showed the variation of energy consumption of L-shape high-rise buildings with width ratio and depth ratio under the weather condition in Hangzhou, China.